The Effect of H2O on the 410-Kilometer Seismic Discontinuity. - Wood, B (1995)
The 410-kilometer seismic discontinuity is generally considered to be caused by a phase transformation of the main constituent of the upper mantle, olivine, alpha-(Mg,Fe)(2)SiO(4), to beta-(Mg,Fe)(2)SiO(4). Recent data show that H(2)O dissolves in olivine and other nominally anhydrous mantle minerals and that the partitioning of H(2)O between olivine and beta-(Mg,Fe)(2)SiO(4) is about 1:10. Such behavior strongly affects the region over which the alpha to beta phase transformation occurs and hence the seismic discontinuity that results. The observed width of the discontinuity constrains the maximum H(2)O content of upper mantle olivine to about 200 parts per million by weight.